From Diagnosis to Management; Mucocele of Stump Appendicitis, Extremely Rare Finding in an Uncommon Surgical Disease: Literature Review. (11th February 2021) - Ali, Syed Muhammad; Al-Tarakji, Mohannad; Shahid, Fakhar; Qabani, Amjad Salah; Shah, Amjad Ali; Ahmed, Khalid; Khan, Muhammad Burhan; Inamullah,
Abstract : Mucocele of the appendix is the accumulation of mucoid material in the appendiceal lumen. Although the terminology is imprecise, as it does not differentiate between the benign and malignant nature of the condition, preoperative recognition is imperative as spillage of the mucus during surgical handling can result in grave complications like pseudomyxoma peritonei. Mucocele developing in a stump of the appendix, i.e., a remnant of appendiceal tissue after surgical removal of an inflamed organ, is an extremely uncommon phenomenon, as not many cases are reported in the literature. In this review, all cases reported in English literature are discussed.